F-REEFS, estructura artificial ajustable al tronco del coral Acropora (A. Palmata, A. Cervicornis), manteniendo una conexión coherente con el contexto y la interacción animal. (2021)
Coral reefs are an ecosystem of great complexity, with a synergy that provides benefits for the environment, animals and the entire marine system, and finally human beings who obtain food and economic sustenance for millions of people who are in these contexts.